Desenvolvimento de peptídeos recombinantes epítopos específicos do Rhipicephalus (Boophilus) microplus selecionados por bibliotecas de Phage Display - Prudencio, Carlos Roberto (2008)
Ticks are implicated in serious economic losses to animal production worldwide in the order of billions of dollars. Although many antigens have been in vaccine tests, none has been effective in the control of ticks, which justifies the development of new antigens as well as new vaccine strategies. Phage Display techniques have been widely employed to map epitope structures, which have served as the basis for developing molecular vaccines. In the present study, we have applied this technique to map specific epitopes of Rhipichephalus (Boophilus) microplus and to validate the peptides as potential immunogens, we have adopted a process of selection prior to final field tests. This strategy was established in order to reduce the number of clones to be tested in the field. Six Phage -displayed random peptide libraries were selected with seven different strategies against the purified hyperimmune serum of chickens (IgY) that were immunized with total proteins of larvae and adults of Rhipicephalus (Boophilus) microplus. The selected Phage clones were sequenced, translated and analyzed through bioinformatics. To evaluate the potential of these phagotopes as effective candidate vaccines, ELISA assays, dot-blot, mice immunization (MI), humoral immune response (HIR) of cattle against the clones and a cutaneous hypersensitivity tests in cattle were performed. The selected Phage clones were analyzed through bioinformatics, generating 107 different peptides in a total of 281 sequences. Some selected phagotopes showed excellent matches with linear sequences of known proteins of the Rhipicephalus (Boophilus) microplus. Peptides that did not present significant matches with known proteins, but shared extensive homology among each other, were clustered and classified as conformational epitopes of Rhipicephalus (Boophilus) microplus, or considered as mimotopes of unknown proteic antigens. Among all clones tested by dot-blots, the 40 most reactive ones were further screened by HIR and MI. The mice sera raised against the Phage clones clearly recognized tick proteins indicating that the phagotope-induced immune responses were antigen-specific, but not all could be identified by the sera of naturally infested cattle (Bos taurus and Bos indicus). Four clones were then selected to go through the cutaneous hypersensitivity tests, and apparently all of them were effectives at diferent degrees. The stringent selection processes coupled with this schemes of validation assays allowed us to narrow down the number of peptides that should be tested in the field. One of the advantages of using whole recombinant M13 virus, carrying the recombinant peptide in fusion with the pIII protein of the virus, is that its capsid acts as adjuvant and could be tested directly without any further mixture. Additionally, we have finally used anergy skin tests (cutaneous hypersensitivity tests) once they are sometimes used to guide clinical decisions. We have assumed that cutaneous hypersensitivity tests measure a common property of cellular immune function relevant to the outcome, which together with the humoral response in naturally infested animals may provide us with sequences of peptides that may be relevant as vaccines. Finally, we have used those sequences to produce multiple antigen peptide system (MAPS), which will be used in future field tests. The present work demonstrates that the whole epitope profile can obtained through screening the Phage Displayed peptide libraries with the hyperimmune serum and reveals the potential of using epitopedisplaying Phage s as peptide vaccines against ticks.